The Antibacterial Activity of Dayak Onion (Eleutherine palmifolia (L.) Merr) towards Pathogenic Bacteria - Tiara Dini Harlita; Oedjijono; Ari Asnani (Tropical Life Sciences Research, 2018)
Antibacterial activity of indigenous Dayak onion (Eleutherine palmifolia (L.) Merr) was investigated. The Dayak onion was solvent extracted with n-hexane, ethyl acetate, and ethanol 96% consecutively. Each extract was tested its antibacterial activity towards methicillin-resistant Staphylococcus aureus (MRSA), Bacillus cereus, Shigella sp., and Pseudomonas aeruginosa using disc diffusion method. The test results showed that the n-hexane, ethyl acetate, and ethanol 96% extracts positively inhibited the growth of MRSA, B. cereus, Shigella sp., and P. aeruginosa. The highest inhibition activity of each extract was obtained with 10 mg/mL of extract concentration; whereas the minimum inhibitory concentration (MIC) of each extract was 2 mg/mL. Extract with the highest inhibition activity was ethyl acetate extract against B. cereus (139.58%). TLC evaluation of ethyl acetate extract showed four spots and bioautography indicated that ethyl acetate extract contained four types of compounds with inhibition activity against B. cereus, in which two compounds have higher antibacterial activity than the other two.